Rare-earth-based polyurethane polishing pad material and preparation method thereof
By mixing oxidatively and using simplified preparation methods in the rare earth polyurethane polishing material, it solves the problem of stretching strength and Shaw's hardness in existing technologies. The effect of high hardness and simplified the process.
Patent Information
- Application Number
- CN202411572905.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-06
AI Technical Summary
While the existing polyurethane polishing pad materials are difficult to improve their Shore hardness while increasing their tensile strength, and the preparation method is relatively cumbersome, which affects its application efficiency.
By mixing oxidatively to a rare earth polyurethane matrix formed by a specific raw material and dosage, and using a simplified preparation method, including the preparation of polymers, the doping of oxidation, and drying molding, it is prepared to have a high stretching extension Rare earth polypeutine polishing material with intensity and high Shaw's hardness.
On the basis of maintaining the hardness of Gao Shao's hardness, the stretch strength of the rare earth polyurethane polishing material is significantly improved. With the doping of 15%oxidative, the stretching strength can reach more than 20MPa, which exceeds the stretching of the commercially available products. The intensity is more than doubled, while simplifying the preparation process and improving application efficiency.
Smart Images

Figure CN119369289A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a rare earth-based polyurethane polishing pad material and a preparation method thereof. Background Art
[0002] Polyurethane material is one of the most commonly used polishing pad materials. During the polishing process, the surface micropores of the polyurethane polishing pad can soften the polishing pad and roughen the surface of the polishing pad, and can keep the abrasive particles in the polishing liquid. Therefore, the polyurethane polishing pad needs to maintain a certain porosity in order to have a good property of storing and transporting the polishing liquid, thereby improving the removal rate of the polished material and the polishing efficiency of the polishing pad. However, from the perspective of the structural physical properties of the polishing pad material, a higher porosity will reduce the density of the polishing pad material, and the mechanical properties will decrease accordingly, which is not conducive to the grinding effect of the polishing pad on the surface of the processed sample, and thus exhibits poor polishing performance.
[0003] Inorganic nanoparticles, such as silica, Janus spheres, carbon black and cerium oxide, as fillers can enhance and toughen the mechanical properties of polyurethane materials. Therefore, when designing the structure of polyurethane materials, inorganic nanoparticles as fillers can be added to polyurethane polymers to dissipate stress, which is beneficial to enhance the elasticity and strength of the polymer matrix at the same time.
[0004] CN118027347A discloses a method for preparing a polyurethane polishing sheet, comprising mixing phosphoric acid and octafluoro-1,6-hexanediol, generating a fluorine-containing phosphate by esterification reaction, and then reacting with melamine to obtain a fluorine-containing phosphate melamine salt; reacting γ-aminopropyltriethoxysilane with succinic anhydride, and modifying nano-silicon dioxide to introduce carboxyl groups on the surface of silicon dioxide; at the same time, grafting the fluorine-containing phosphate melamine salt onto the surface of carboxylated silicon dioxide under the action of a condensing agent, dicyclohexylcarbodiimide, thereby obtaining modified silicon dioxide; mixing and slicing the modified silicon dioxide with polyurethane to obtain a polyurethane polishing sheet. Although the polyurethane polishing sheet prepared by the preparation method has a high tensile strength, its Shore hardness still needs to be improved, and the preparation method is relatively cumbersome.
[0005] CN109517527A discloses a wear-resistant polishing material, which is composed of 100 parts by weight of polyether polyol, 100 parts by weight of diisocyanate, 1-2 parts by weight of bisphenol A epoxy resin, 3-5 parts by weight of short-cut nylon fiber, 4-6 parts by weight of chitin, 2-3 parts by weight of silicone oil, 2-3 parts by weight of chlorinated paraffin, 1-2 parts by weight of ethylene glycol, 10-15 parts by weight of maleic anhydride grafted polypropylene, 0.5-1 parts by weight of dimethylcyclohexylamine, 2-4 parts by weight of acetone, 2-3 parts by weight of shell powder, 1-2 parts by weight of rutile titanium dioxide, 1-1.5 parts by weight of hollow silica-alumina microbeads, 2-3 parts by weight of zinc stearate, 1-2 parts by weight of tris(2,4-di-tert-butylphenyl)phosphite, 1-2 parts by weight of antioxidant 1010, 0.5-1 parts by weight of carbodiimide and 4-8 parts by weight of cerium oxide. The tensile strength of the wear-resistant polishing material is low.
[0006] CN115284165A discloses a porous polyurethane polishing pad and a preparation method thereof, wherein the porous polyurethane polishing pad comprises the following raw materials in parts by weight: 70-110 parts of polyether polyol, 300-400 parts of carbodiimide modified 4,4'-diphenylmethane diisocyanate, 20-30 parts of 1,4-butanediol, 20-30 parts of 3,3-dichloro-4,4'-diaminodiphenylmethane, 15-18 parts of cerium oxide, 5-7 parts of carbon black, 2-5 parts of dibutyltin dilaurate, 2-5 parts of triethylamine, 8-10 parts of deionized water and 13-15 parts of pore stabilizer. The Shore hardness of the polyurethane polishing pad is relatively low. Summary of the invention
[0007] In view of this, one object of the present invention is to provide a method for preparing a rare earth-based polyurethane polishing pad material, wherein the rare earth-based polyurethane polishing pad material prepared by the preparation method has a relatively high Shore hardness and a significantly improved tensile strength. Another object of the present invention is to provide a rare earth-based polyurethane polishing pad material prepared by the above preparation method. The present invention adopts the following technical scheme to achieve the above object.
[0008] In one aspect, the present invention provides a method for preparing a rare earth-based polyurethane polishing pad material, comprising the following steps:
[0009] 1) polytetrahydrofuran, alkyl diisocyanate, organotin catalyst and first organic solvent are mixed and reacted at 55-65° C. for 6-11 hours to obtain a preliminary reactant; a diol chain extender is added to the preliminary reactant and the reaction is continued at 55-65° C. for 4.5-9 hours, and after the reaction is completed, the reaction is cooled to obtain a reaction mixture; the reaction mixture is placed in an alkane solvent for precipitation to obtain a solid; the solid is dried to obtain a polymer;
[0010] 2) dissolving the polymer in a second organic solvent to obtain a polymer solution; mixing the polymer solution with cerium oxide to obtain a mixture;
[0011] 3) transferring the mixture into a mold and drying it to obtain a rare earth-based polyurethane polishing pad material;
[0012] Wherein, the molar ratio of polytetrahydrofuran, alkyl diisocyanate, organotin catalyst, diol chain extender and first organic solvent is 100-200:100-200:1-5:10-20:3000-5000;
[0013] Wherein, the first organic solvent is selected from tetrahydrofuran or 2-methyltetrahydrofuran;
[0014] Wherein, the second organic solvent is selected from one of dichloromethane, chloroform and carbon tetrachloride;
[0015] The mass of the cerium oxide is 13-30 wt % of the mass of the polymer in the polymer solution.
[0016] According to the preparation method of the present invention, preferably, the molecular weight of the polytetrahydrofuran is greater than or equal to 650 and less than 1000.
[0017] According to the preparation method of the present invention, preferably, in step 1), the alkyl diisocyanate is selected from one of 1,6-hexamethylene diisocyanate, dicyclohexylmethane diisocyanate and isophorone diisocyanate.
[0018] According to the preparation method of the present invention, preferably, in step 1), the organic tin catalyst is selected from one of dibutyltin dilaurate, dibutyltin diacetate, dioctyltin diacetate, stannous octoate and dibutyltin maleate.
[0019] According to the preparation method of the present invention, preferably, in step 1), the diol chain extender is selected from one of ethylene glycol, 1,4-butanediol, diethylene glycol, 1,6-hexanediol and 1,3-propylene glycol.
[0020] According to the preparation method of the present invention, preferably, in step 1), the first organic solvent is tetrahydrofuran; and the alkane solvent is selected from one of n-hexane, n-heptane and cyclohexane.
[0021] According to the preparation method of the present invention, preferably, in step 2), the second organic solvent is dichloromethane; and the mass ratio of the polymer to the second organic solvent is 1-2:3-10.
[0022] According to the preparation method of the present invention, preferably, in step 2), the mass of the cerium oxide is 15-25wt% of the mass of the polymer in the polymer solution.
[0023] According to the preparation method of the present invention, preferably, in step 1), the solid is vacuum dried at 50-80°C for 3-8 hours to obtain a polymer; in step 3), the mixture is dripped into a mold and then vacuum dried at 30-60°C for 10-30 hours to obtain a rare earth-based polyurethane polishing pad material.
[0024] On the other hand, the present invention also provides a rare earth-based polyurethane polishing pad material, which is prepared according to the preparation method described above.
[0025] The rare earth-based polyurethane polishing pad material prepared by the preparation method of the present invention has a significantly higher tensile strength on the basis of having a higher Shore hardness. When doped with 15% cerium oxide, the tensile strength can reach more than 20 MPa, which is more than double the tensile strength of the commercially available rare earth polyurethane polishing pad material. Furthermore, the rare earth-based polyurethane polishing pad material of the present invention has a significant pore structure. In addition, the preparation method of the present invention is relatively simple to operate, the process flow is not complicated, and it is conducive to popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The following are Fourier transform infrared spectra of the products obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2.
[0027] Figure 2 These are cross-sectional pore scanning images of the products obtained in Example 1, Example 2, Comparative Example 1, and Comparative Example 2.
[0028] Figure 3 It is a cross-sectional scan of the products obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2.
[0029] Figure 4 This is a Shore A hardness diagram of the products obtained in Example 1, Example 2, Comparative Example 1, and Comparative Example 2.
[0030] Figure 5 This is a graph of the tensile strength of the products obtained in Example 1, Example 2, Comparative Example 1, and Comparative Example 2. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0032] In the present invention, a certain amount of cerium oxide is doped into a polyurethane polymer matrix formed by specific raw materials and dosages to obtain a rare earth-based polyurethane polishing pad material having significantly higher tensile strength on the basis of higher Shore hardness. This is not a conventional choice.
[0033] The preparation method of the rare earth-based polyurethane polishing pad material of the present invention comprises the following steps:
[0034] (1) polymer preparation step; (2) cerium oxide doping step; (3) drying and molding step. The following is a detailed description.
[0035] <Polymer Preparation Step>
[0036] The polytetrahydrofuran, alkyl diisocyanate, organic tin catalyst and first organic solvent are mixed and reacted at 55-65°C for 6-11 hours to obtain a preliminary reactant; a diol chain extender is added to the preliminary reactant and the reaction is continued at 55-65°C for 4.5-9 hours, and the reaction is cooled after completion to obtain a reaction mixture; the reaction mixture is placed in an alkane solvent for precipitation to obtain a solid; the solid is dried to obtain a polymer. Such a polymer, when doped with cerium oxide, can be beneficial for obtaining a rare earth-based polyurethane polishing pad composite material having both high Shore hardness and tensile strength.
[0037] In the present invention, polytetrahydrofuran is also known as polytetramethylene ether glycol, which can be abbreviated as PTMG, and has a molecular weight greater than or equal to 650 and less than 1000, for example, 650.
[0038] In the present invention, the alkyl diisocyanate is selected from one of 1,6-hexamethylene diisocyanate, dicyclohexylmethane diisocyanate and isophorone diisocyanate, preferably 1,6-hexamethylene diisocyanate (abbreviated as HDI). The present invention finds that the polymer obtained by using such diisocyanate is more conducive to improving the tensile strength of the obtained rare earth-based polyurethane polishing pad material when doped with cerium oxide. If toluene-2,4-diisocyanate and diphenylmethane diisocyanate are used, the technical effect of the present invention cannot be achieved.
[0039] In the present invention, the organotin catalyst is selected from one of dibutyltin dilaurate, dibutyltin diacetate, dioctyltin diacetate, stannous octoate and dibutyltin maleate, preferably dibutyltin dilaurate.
[0040] In the present invention, the diol chain extender is selected from one of ethylene glycol, 1,4-butanediol, diethylene glycol, 1,6-hexanediol and 1,3-propylene glycol, preferably 1,4-butanediol. The present invention finds that the use of a diol chain extender is more conducive to obtaining a rare earth-based polyurethane polishing pad material with higher Shore hardness and tensile strength.
[0041] In the present invention, the first organic solvent is selected from tetrahydrofuran or 2-methyltetrahydrofuran, preferably tetrahydrofuran.
[0042] In the present invention, the molar ratio of polytetrahydrofuran, alkyl diisocyanate, organotin catalyst, diol chain extender and first organic solvent is 100-200:100-200:1-5:10-20:3000-5000, preferably 40-100:40-100:1:10-20:1500-4000, more preferably 50-80:50-80:1:10-15:1700-3000, further preferably 60-70:60-70:1:11-14:1700-2500.
[0043] In the present invention, the temperature of the preliminary reaction may be 55 to 65° C., preferably 58 to 65° C., more preferably 60 to 65° C. The time of the preliminary reaction may be 6 to 11 hours, preferably 7 to 10 hours, more preferably 8 to 9 hours. A preliminary reactant is obtained.
[0044] In the present invention, the diol chain extender is added to the preliminary reactants and the reaction is continued. The temperature for the continued reaction may be 55 to 65° C., preferably 58 to 65° C., and more preferably 60 to 65° C. The continued reaction time may be 4.5 to 9 hours, preferably 5.5 to 8 hours, and more preferably 6 to 7 hours. After the continued reaction is completed, the mixture is cooled to room temperature to obtain a reaction mixture.
[0045] In the present invention, the reaction mixture is added dropwise to an alkane solvent for precipitation to obtain a solid. The alkane solvent is selected from one of n-hexane, n-heptane and cyclohexane, preferably n-hexane. When the reaction mixture is added dropwise to the alkane solvent, a solid is precipitated, and the solid is filtered and precipitated to obtain a solid. The solid can be repeatedly precipitated into a clean alkane solvent, filtered, and the solid is collected. This can be repeated two to three times. This is conducive to improving the purity.
[0046] In the present invention, the solid can be vacuum dried at 50 to 80° C. for 3 to 8 hours to obtain a polymer. Preferably, the solid is dried in a vacuum drying oven. The vacuum drying temperature is preferably 55 to 75° C., more preferably 60 to 65° C. The vacuum drying time is preferably 5 to 8 hours, more preferably 5 to 7 hours.
[0047] <Cerium Oxide Doping Step>
[0048] The polymer is dissolved in a second organic solvent to obtain a polymer solution; the polymer solution is mixed with cerium oxide to obtain a mixture. This is conducive to uniform dispersion of cerium oxide. In addition, the present invention finds that if cerium oxide is added in the polymerization reaction step, it is not conducive to forming a rare earth-based polyurethane polishing pad material with both high Shore hardness and tensile strength.
[0049] In the present invention, the second organic solvent is selected from one of dichloromethane, chloroform and carbon tetrachloride, preferably dichloromethane. The mass ratio of the polymer to the second organic solvent is 1-2:3-10, preferably 1:2.5-7, and more preferably 1:2.6-5.5.
[0050] In the present invention, the cerium oxide is nano-cerium oxide, and its particle size is 500-800nm.
[0051] According to one embodiment of the present invention, cerium oxide is added to a polymer solution to obtain a mixture; wherein the mass of cerium oxide is 13-30wt% of the mass of the polymer in the polymer solution, preferably 15-25wt%, more preferably 17.6-22wt%, and further preferably 17.6-20wt%. Such a cerium oxide doping amount can not only make the obtained rare earth-based polymer polishing pad material have a higher Shore hardness, but also significantly improve its tensile strength, while taking into account the cost.
[0052] <Drying and molding step>
[0053] The mixture is transferred into a mold and dried to obtain a rare earth-based polyurethane polishing pad material, which is conducive to the stability of the performance of the rare earth-based polyurethane polishing pad material.
[0054] According to a specific embodiment of the present invention, the mixture is dripped into a mold and then vacuum dried at 30 to 60° C. for 10 to 30 hours to obtain a rare earth-based polyurethane polishing pad material.
[0055] In the present invention, after the mixture is dripped into the mold, it can be left at room temperature for 2 to 10 hours to allow the solvent to evaporate, and then vacuum dried at 30 to 60° C. The mold can be a Teflon mold.
[0056] In this step, the drying is preferably carried out in a vacuum drying oven, and the vacuum drying temperature is preferably 35 to 55° C., more preferably 40 to 50° C. The vacuum drying time is preferably 15 to 30 hours, more preferably 20 to 25 hours.
[0057] The rare earth-based polyurethane polishing pad material of the present invention is a polyurethane polishing pad material doped with cerium oxide, which has a higher tensile strength on the basis of having a higher Shore hardness. In addition, the rare earth-based polyurethane polishing pad material of the present invention has an obvious pore structure. Such a rare earth-based polyurethane polishing pad material is conducive to improving polishing efficiency.
[0058] The test methods used in the following examples and comparative examples are described as follows:
[0059] Shore A Hardness: Tested using LX-A Shore Hardness Tester.
[0060] Tensile strength: tested using a CMT6103 electronic universal testing machine.
[0061] Infrared spectrum: tested by Bruker Alph infrared spectrometer in reflection mode, with a test range of 500-4000cm -1 .
[0062] Thermogravimetric test: The data were measured using a Mettler TGA2 thermogravimetric analyzer.
[0063] Scanning test: The test was conducted using a German Zeiss Sigma 500 field emission scanning electron microscope.
[0064] The raw materials used in the following examples and comparative examples are described as follows:
[0065] The molecular weight of polytetrahydrofuran PTMG650 is 650, which is purchased from Shanghai Titan Technology Co., Ltd. The cerium oxide used is nano cerium oxide with a particle size of 500-800 nm, which is purchased from Baotou Haorui Rare Earth Co., Ltd.
[0066] Example 1
[0067] Add polytetrahydrofuran PTMG650 (32.5 g, 0.05 mol), 1,6-hexamethylene diisocyanate (HDI) (8.4 g, 0.05 mol), dibutyltin dilaurate (0.5 g, 0.8 mmol) and 120 mL of tetrahydrofuran into a reaction bottle, stir until well mixed, and react at 60°C for 8 h to obtain a preliminary reactant; add 1,4-butanediol (0.9 g, 0.01 mol) to the preliminary reactant, and continue to react at 60°C for 6 h; after the reaction is completed, cool to room temperature to obtain a reaction mixture; add the reaction mixture dropwise into n-hexane for sedimentation, separate the solid obtained by sedimentation, and repeat the sedimentation twice to collect the solid; place the solid in a vacuum drying oven and vacuum dry it at 60°C for 6 h to obtain a polymer.
[0068] 3 g of the polymer prepared above was dissolved in 8 mL of dichloromethane to obtain a polymer solution; 450 mg of cerium oxide was added to the polymer solution, and the mixture was stirred and mixed to obtain a mixture; the mixture was dripped into a Teflon mold (50 mm×50 mm×5 mm), the solvent therein was volatilized at 30° C. for 2 h, and then vacuum dried at 40° C. for 24 h to obtain a rare earth-based polyurethane polishing pad material, which was recorded as RPU. The cerium oxide content in the RPU was 13.0 wt%.
[0069] Example 2
[0070] The only difference from Example 1 is that the amount of cerium oxide used is different. In this example, 600 mg of cerium oxide is used. The remaining steps and parameters are the same as those in Example 1. The obtained rare earth-based polyurethane polishing pad material is recorded as RPU-2. The cerium oxide content in RPU-2 is 16.7 wt%.
[0071] Comparative Examples 1-2
[0072] The only difference from Example 1 is that the amount of cerium oxide is different. In Comparative Example 1, the amount of cerium oxide is 0, and the resulting polyurethane material is recorded as RPU-0. In Comparative Example 2, the amount of cerium oxide is 300 mg, and the resulting polyurethane polishing pad material is recorded as RPU-1, and the cerium oxide content in RPU-1 is 9.1 wt%.
[0073] Table 1
[0074]
[0075] Table 2
[0076]
[0077] Characterization and performance testing
[0078] 1) Infrared test
[0079] The products obtained from Comparative Example 1, Comparative Example 2, Example 1 and Example 2 were tested by Fourier transform infrared spectroscopy. Figure 1 The 2260-2270 cm -1 The NCO characteristic peak at 3300 cm-1 indicates that the isocyanate monomer has reacted completely. -1 The stretching vibration peak of NH at 1700 cm -1 The stretching vibration peak of carbonyl at 1556 cm -1 The amide II band is the combination of NH bond bending vibration and CN bond stretching vibration. These are the characteristic peaks of urea groups, proving the successful synthesis of the polyurethane backbone.
[0080] In addition, the product obtained in Comparative Example 2, Example 1, and Example 2 can detect 763 cm -1 These results show that the rare earth-based polyurethane polishing pad material has been successfully prepared.
[0081] 2) Thermogravimetric test
[0082] Comparative Example 1, Comparative Example 2, and Example 2 were subjected to thermogravimetric tests. From the results, it can be seen that the polyurethane sample without cerium oxide added has a residual rate of 0.6% in the thermogravimetric test at 700°C in a nitrogen atmosphere, while the residual rates of the polyurethane polishing pad composite material with different amounts of cerium oxide added are 12.6% and 15.08%, respectively. As the cerium oxide content increases, the residual rate of the composite material gradually increases.
[0083] 3) Cross-sectional pore scanning
[0084] The products obtained from Comparative Example 1, Comparative Example 2, Example 1, and Example 2 (i.e., RPU-0, RPU-1, RPU, and RPU-2) were subjected to cross-sectional pore scanning. The results are shown in FIG. Figure 2 As can be seen from the figure, there is an obvious pore structure in the rare earth-based polyurethane polishing pad material prepared by the present invention. The dense pore structure is conducive to improving the surface hardness of the polyurethane polishing pad material, and can be more fully in contact with the polishing liquid during the polishing process, thereby improving the polishing efficiency of the polishing material.
[0085] 4) Cross-sectional scan
[0086] The products obtained in Comparative Example 1, Comparative Example 2, Example 1 and Example 2 (i.e., RPU-0, RPU-1, RPU, and RPU-2) were subjected to cross-sectional scanning, and the morphology of the fractured cross-section of the polyurethane polishing pad film was characterized by scanning electron microscopy (SEM). The cross-sectional scanning results are shown in FIG. Figure 3 It can be clearly observed from the figure that, compared with RPU-0 without cerium oxide addition, cerium oxide particles are obviously present in the other three samples, and the cerium oxide particles are well dispersed in the polyurethane matrix, and increase with the increase of cerium oxide addition.
[0087] 5) Shore A hardness
[0088] The products obtained from Comparative Example 1, Comparative Example 2, Example 1 and Example 2 (i.e. RPU-0, RPU-1, RPU, RPU-2) were subjected to Shore hardness test. The results are shown in Figure 4 .Depend on Figure 4 It can be seen that with the increase of cerium oxide content, the surface hardness of the material gradually increases. This should be because the cerium oxide particles can withstand a larger load and make the material show a greater surface hardness. This shows that by increasing the content of cerium oxide, the surface hardness of the polyurethane material can be effectively improved.
[0089] 6) Tensile strength test
[0090] The products obtained from Comparative Example 1, Comparative Example 2, Example 1 and Example 2 (i.e., RPU-0, RPU-1, RPU, RPU-2) were subjected to tensile strength tests. Specifically, each product was cut into dumbbell-shaped strips with a length of 50 mm, a width of 4 mm, and a thickness of 2 mm using a dumbbell cutter for further testing. The tensile strength and other data during the stretching process were collected using an electronic universal testing machine. The results are shown in Figure 5 .Depend on Figure 5 and Figure 4 It can be seen that the tensile strength of the cerium oxide-doped rare earth polyurethane polishing pad material obtained by the present invention can reach more than 20 MPa, and the Shore hardness can reach more than 80 A. Compared with the commercially available polyurethane rare earth polishing pad (the content of cerium oxide is 15wt%, and the amount of cerium oxide added in the commercially available polyurethane rare earth polishing pad is based on the total mass of the polishing pad) (its Shore hardness is 85A and the tensile strength is 4.32 MPa), the Shore hardness of the rare earth polyurethane polishing pad material of the present invention is basically the same, but the tensile strength is greatly improved, and its tensile strength is about 5 times that of the commercially available polyurethane rare earth polishing pad, or even 5 times as much.
[0091] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be thought of by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing a rare earth-based polyurethane polishing pad material, characterized in that: The steps include: 1) polytetrahydrofuran, alkyl diisocyanate, organotin catalyst and first organic solvent are mixed and reacted at 55-65° C. for 6-11 hours to obtain a preliminary reactant; a diol chain extender is added to the preliminary reactant and the reaction is continued at 55-65° C. for 4.5-9 hours, and after the reaction is completed, the reaction is cooled to obtain a reaction mixture; the reaction mixture is placed in an alkane solvent for precipitation to obtain a solid; the solid is dried to obtain a polymer; 2) dissolving the polymer in a second organic solvent to obtain a polymer solution; mixing the polymer solution with cerium oxide to obtain a mixture; 3) transferring the mixture into a mold and drying it to obtain a rare earth-based polyurethane polishing pad material; Wherein, the molar ratio of polytetrahydrofuran, alkyl diisocyanate, organotin catalyst, diol chain extender and first organic solvent is 100-200:100-200:1-5:10-20:3000-5000; Wherein, the first organic solvent is selected from tetrahydrofuran or 2-methyltetrahydrofuran; Wherein, the second organic solvent is selected from one of dichloromethane, chloroform and carbon tetrachloride; The mass of the cerium oxide is 13-30 wt % of the mass of the polymer in the polymer solution.
2. The preparation method according to claim 1, characterized in that: The molecular weight of the polytetrahydrofuran is greater than or equal to 650 and less than 1000.
3. The preparation method according to claim 1, characterized in that: In step 1), the alkyl diisocyanate is selected from one of 1,6-hexamethylene diisocyanate, dicyclohexylmethane diisocyanate and isophorone diisocyanate.
4. The preparation method according to claim 1, characterized in that: In step 1), the organotin catalyst is selected from one of dibutyltin dilaurate, dibutyltin diacetate, dioctyltin diacetate, stannous octoate and dibutyltin maleate.
5. The preparation method according to claim 1, characterized in that: In step 1), the diol chain extender is selected from one of ethylene glycol, 1,4-butanediol, diethylene glycol, 1,6-hexanediol and 1,3-propylene glycol.
6. The preparation method according to claim 1, characterized in that: In step 1), the first organic solvent is tetrahydrofuran; and the alkane solvent is selected from one of n-hexane, n-heptane and cyclohexane.
7. The preparation method according to claim 1, characterized in that: In step 2), the second organic solvent is dichloromethane; the mass ratio of the polymer to the second organic solvent is 1-2:3-10.
8. The preparation method according to claim 1, characterized in that: In step 2), the mass of the cerium oxide is 15-25 wt % of the mass of the polymer in the polymer solution.
9. The preparation method according to claim 1, characterized in that: In step 1), the solid is vacuum dried at 50-80° C. for 3-8 hours to obtain a polymer; in step 3), the mixture is dripped into a mold and then vacuum dried at 30-60° C. for 10-30 hours to obtain a rare earth-based polyurethane polishing pad material.
10. A rare earth-based polyurethane polishing pad material, characterized in that: The invention relates to a novel nanostructured carbon foam prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Wear-resistant polishing material
CN109517527A
High-wear-resistance polyurethane polished section and preparation process thereof
CN118027347A
Manufacturing method of polyurethane polishing pad
CN104385120A
Preparation method of cerium oxide based polishing synthetic paper
CN106519644A
CMP polishing layer based on porous cerium oxide and preparation method thereof
CN109015341A